2021
DOI: 10.3168/jds.2020-18823
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil supplementation and starter protein content: Effects on growth performance, digestibility, ruminal fermentation, and urinary purine derivatives of Holstein dairy calves

Abstract: This study investigated the effects of feeding dairy calves starter diets containing 19% or 22% crude protein (CP) content on a dry matter basis and either supplemented or not with soybean oil (SBO, 0 vs. 3%, dry matter basis) on growth performance, digestibility, urinary nitrogen, and purine derivatives (PD) excretion. A total of 48 female Holstein dairy calves (mean 39.8 kg of body weight) were randomly distributed to experimental diets in a 2 × 2 factorial arrangement of treatments. The 4 dietary treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…It seems that the lower ADG in FO-fed calves is mostly related to lower starter intake, as observed in the present study or the above-mentioned studies. However, it is notable that environmental conditions (heat stress, cold stress and thermo-neutral conditions) and method of oil delivery (mixed with milk replacer or mixed with a starter such as Ca salt) can also influence the obtained results (5,6) .…”
Section: Growth Performance Feed Efficiency and Total Tract Digestibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…It seems that the lower ADG in FO-fed calves is mostly related to lower starter intake, as observed in the present study or the above-mentioned studies. However, it is notable that environmental conditions (heat stress, cold stress and thermo-neutral conditions) and method of oil delivery (mixed with milk replacer or mixed with a starter such as Ca salt) can also influence the obtained results (5,6) .…”
Section: Growth Performance Feed Efficiency and Total Tract Digestibilitymentioning
confidence: 99%
“…Generally, carbohydrates prepare the primary source of energy in starter diets for young calves. Although some research indicated negative effects of supplemental fat on dairy calf growth performance, this was mainly due to the detrimental effects of fat on nutrient digestibility, ruminal fermentation and microbial activity (5,6) ; however, positive results have been obtained when calves received different supplemental fat, such as essential fatty acid (FA) (7) or n-3 FA, supplied through linseed oil (LSO) in starter diets (8) . Discrepancies among studies that have evaluated fat incorporation in calves' diets can be related to many factors, such as fat feeding levels, fat delivery methods through a liquid or solid feed, starter processing methods or individual FA profiles of the supplemented fat (2) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We suspected that the level of milk feeding may influence estimated microbial growth through factors such as intake of starters and changing the ratio CP:ME. In addition, bovine milk contains purines (Gonzalez-Ronquillo et al, 2003), which may affect the results of estimated microbial yield from urinary purine derivatives (PD) in milkfed dairy calves (Yousefinejad et al, 2021), which has not been considered thus far for different milk feeding levels. Funaba et al (1995) evaluated urinary excretion of PD immediately after weaning and indicated that urinary excretion of PD was atypical 1 wk after weaning, compared with calves at 6 wk of age.…”
Section: Introductionmentioning
confidence: 99%